Physics of humping formation in laser powder bed fusion - Tang, C.; Le, K.Q.; Wong, C.H. (International journal of heat and mass transfer, 2020)
•Implementation of ray tracing heat source in the CFD model•Good consistency between simulations and experiments•Humping defects in samples fabricated at high laser power and scanning speed•Discussion on the roles of various force on humping formation Despite of the promising attributes of laser powder bed fusion, part quality such as porosity and surface roughness remains a critical issue for industrial applications. Humping is a surface defect that may greatly deteriorate the mechanical performances of as-built components. However, current understanding of humping formation remains vague and unclear. In this respect, laser powder bed fusion of stainless steel 316 L single tracks was simulated by using computational fluid dynamics. With the same linear energy density, the simulated tracks exhibit irregular humps at high scanning velocities, which is validated against experiments. In addition, flow kinetics was analyzed to elucidate the physical origins of humping formation during printing process. The study reveals the various effects of surface tension, Marangoni shear force, viscous force and recoil pressure on the humping phenomenon in laser powder bed fusion. At relatively high scanning speed, a swelling with large contact angle is formed due to the competition between surface tension and flow inertia. Capillary instability divides the swelling into separated regions, which is responsible for the humping formation during printing process.